PHENOTYPIC AND MOLECULAR CHARACTERISATION OF SOME AMARANTHUS ACCESSIONS AND HEPATOPROTECTIVE ACTIVITY OF THEIR ETHANOL EXTRACT ON SODIUM ARSENITE-INDUCED TOXICITY IN MALE RATS (2013)
Amaranth is an underutilised crop with great potential as a source of essential nutrients. It also contains bioactive compounds with potential health benefits. However, its characterisation for agronomic and nutritional traits is limited. Likewise, information on its hepatoprotective potential is scarce. In this study Amaranthus accessions were characterised using phenotypic and molecular markers. The quality of its seed protein and hepatoprotective activity of its Ethanol Seed Extract (ESE) on sodium arsenite (NaAS)-induced toxicity in male rats were also investigated. Twenty-nine accessions (27 from the United States Agricultural Research Station and 2 from National Horticultural Research Institute, Ibadan) were characterised using 27 phenotypic traits and 16 Random Amplified Polymorphic DNA (RAPD) primers. Protein quality was assessed using Kjedahl method, amino acid analyzer and one-dimensional electrophoresis. The ESE of all accessions were analysed for phytochemical contents and antioxidant activities. Two out of the 29 accessions with the highest nutritional contents were used for hepatoprotective study. Experimental design consisted of two main groups (representing the two accessions), each consisting of eight treatment groups of 5 rats each. Treatment groups comprised of control, NaAS (2.5mg/kg body weight), amaranth seed extracts (100, 200, 300 mg/kg body weight) and NaAS plus amaranth seed extracts (100, 200, 300 mg/kg). After 14 days of treatment, serum Alanine Aminotransferase (ALT) and Gamma Glutamyl Transferase (GGT) activities were assayed spectrophotometrically. Hepatic Superoxide Dismutase (SOD), Catalase and Glutathione Peroxidase (GPx) activities were assayed likewise. Data were analysed using ANOVA and Cluster at p=0.05. For phenotypic traits, 57.5% variability was observed and accessions were grouped into five clusters. The RAPD analysis yielded 193 loci. Genetic similarity coefficient ranged from 0.6 to 0.9 while dendogram grouped accessions into nine clusters. Total protein contents ranged from 11.8 to 19.0%. Total essential amino acids ranged from 31.2 to 44.9% and were limited in tryptophan and leucine. Albumin, globulin and glutelin were the major protein fractions. Phytate, total flavonoid, total polyphenol, 2, 2-diphenyl-1-picrylhydrazyl (DPPH), total antioxidant and 2, 2-azino-bis-3-ethylbenz-thiazoline-6-sulfonate (ABTS) values ranged from 0.8-1.9%; 7.8-11.0mg/100g; 23.9-35.4mg/100g; 82.8-95.4%; 111.3-271.6%; 157.6-208.8mM Trolox Equivalent (TE), respectively. Accessions A23 (Amaranthus hypochondriacus, AHC) and A28 (Amaranthus hybridus, AHB) had higher protein and phytochemical contents than the other accessions. The activities of ALT (16.7±1.0U/L) and GGT (3.5±0.9U/L) in NaAS-treated group were significantly higher than control (ALT - 9.4±1.3U/L, GGT - 1.7±0.7U/L) and lower in groups treated with AHC plus NaAS (100mg/kg - 14.1±0.8U/L, 3.2±0.6U/L), (200mg/kg - 12.6±0.3U/L, 2.6±1.1U/L) and (300mg/kg - 9.2±0.2U/L, 1.7±0.7U/L). Activities of ALT and GGT were also lower in AHB plus NaAS treated groups (100mg/kg - 12.5±1.4U/L, 2.9±0.7U/L), (200mg/kg - 11.8±0.8U/L, 2.3±0.9U/L), and (300mg/kg - 8.6±2.7U/L, 1.8±0.6U/L) when compared with NaAS-treated group. Hepatic SOD, Catalase and GPx activities were significantly lower in NaAS-treated group when compared with control and groups administered different doses of the amaranth extracts. Amaranth accessions A23 (Amaranthus hypochondriacus) and A28 (Amaranthus hybridus) contained a good balance of essential amino acids and the ethanol extract showed dose-dependent hepatoprotective activity. The diverse clusters can be used as parents in hybridization programmes.